2012
DOI: 10.2139/ssrn.2163517
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Regime Shifts and the US Subprime Bubble

Abstract: China's economic development in recent decades has been tremendous, but subject to debate. This paper calculates regional prices that make incomes comparable across both time and space using the Engel-curve approach. Incomes are adjusted using these price indices, providing new estimates of inequality and poverty development. Our findings contrast with measures based on the official consumer price indices (CPIs) -in a time characterized by high economic growth, we find a larger increase in inequality and a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…modeled by the lagged house price appreciation terms. A similar assumption has been made in Abraham and Hendershott (1996), Gallin (2008), Anundsen and Jansen (2013) and Anundsen (2013). This assumption is also consistent with the view that lagged house price appreciation does not have permanent effects, but rather that it picks up a momentum, or a "bubble builder" effect, to use the terminology of Abraham and Hendershott (1996).…”
Section: Theoretical Backgroundsupporting
confidence: 78%
See 2 more Smart Citations
“…modeled by the lagged house price appreciation terms. A similar assumption has been made in Abraham and Hendershott (1996), Gallin (2008), Anundsen and Jansen (2013) and Anundsen (2013). This assumption is also consistent with the view that lagged house price appreciation does not have permanent effects, but rather that it picks up a momentum, or a "bubble builder" effect, to use the terminology of Abraham and Hendershott (1996).…”
Section: Theoretical Backgroundsupporting
confidence: 78%
“…is equal across regional markets, and that it can be approximated by the evolution of the real national interest rate, i.e.Ũ C j = R ∀ j, where R denotes the real interest rate. 1 The credit constraint variable is unobservable, but Anundsen (2013) has shown that the expansion of subprime borrowing became an important driver of national US house prices in the previous decade. 2 Consistent with this, we assume that CC j = CC ∀ j, where CC is proxied by the share of new loan originations that are given to the subprime segment (CC = SP ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding a little more to the investigation of the role of real estate prices on the economy, Musso et al (2011), Xiao (2013), Sun and Tsang (2014), Mora-Sanguinetti and Rubio (2014), Ngo (2015) and Zhu et al (2017) modeled monetary policy; Li et al (2015) examined the co-movement and causal relationships between the real estate market and the US stock market; Mora-Sanguinetti and Rubio (2014) and Alpanda and Zubairy (2016) checked the effects of housing policies, for example, subsidies on home-ownership acquisition; Rubio and Carrasco-Gallego (2016) and Falagiarda and Saia (2017) investigated macroprudential policy, such as changes in the Basel rules 1, 2 and 3 and endogenous loan-to-value (LTV) parameters with systemic and idiosyncratic risks, respectively; Anundsen (2015) and Suh and Walker (2016) studied new ex-post explanations for the Subprime crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Geanakoplos (2010b) documents the decrease in down payment on subprime mortgages and its correlation with the Case-Shiller house price index. The increased lending from subprime mortgage originators and the securitization process are documented in more detail in the Financial Crisis Inquiry Report (2011); see alsoHaughwout-Peach-Tracy (2008) Anundsen (2014). shows that the econometric relation between house prices and rents, or between houses prices and fundamentals (income, interest rates, housing stock, taxes), with a start date of 1975 is stable when the end point of the series is taken anywhere between 1995 and 2000, but becomes unstable in the early 2000s, in particular after 2003.…”
mentioning
confidence: 99%